Uma proposta pedagógica para melhorar a aprendizagem e os resultados do SIMAIS em matemática - Andrade, Francisco de Assis de Oliveira (2024)
The present work aims to analyze the impact of a pedagogical proposal based on Active Learning Methodologies on the results of SIMAIS/RN in the area of Mathematics. Thus, the research is focused on improving learning and results of the Integrated Institutional Monitoring and Evaluation System of Rio Grande do Norte, SIMAIS/RN in Mathematics, specifically at the Monsenhor Joaquim Honório State School, located in the Municipality of Guamaré/RN. To this end, we propose a pedagogical intervention based on integrative learning planning to improve student performance in external assessments and restore interest in Mathematics. Mathematics Education faces significant challenges in the current context, where students' motivation and interest are often affected by traditional and outdated teaching methods. The work in question addresses this reality with a pedagogical proposal aimed at revitalizing Mathematics teaching at the Monsenhor Joaquim Honório State School, with a special focus on the SIMAIS/RN results. The research identifies the need for a pedagogical intervention that goes beyond the standard curriculum, incorporating Active Learning Methodologies to engage students more effectively. The study adopts a mixed approach, combining quantitative and qualitative analysis to assess the impact of the implemented strategies. The results discussed reveal a significant increase in student performance in the SIMAIS/RN assessments after the implementation of the pedagogical intervention. Furthermore, there was an increase in students' interest in Mathematics, indicated by greater participation in the proposed activities and positive feedback. The suggested intervention proved to be an appropriate strategy to improve not only academic results, but also to revive students' interest in the subject.